Artificial intelligence in biology and learning biology: A literature review - Aripin, Ipin; Gaffar, Aden Arif; Jabar, Muhammad Barin Abdul; Yulianti, Diana (Jurnal Mangifera Edu, 2024)
Artificial Intelligence (AI) had been developed in various fields of human life. The use of AI brought the world towards a digital transformation that had not been imagined before. One form of AI development in the fields of biology and biology education brought the development of science in both fields far beyond expectations. The use of AI in the fields of biology and biology education had utilized many new methods and discoveries that are beneficial to humans. The purpose of this study was to determine the application of AI in biology and biology learning. The literature review method was used to analyze and synthesize research results from a new perspective. The results of the analysis of various pieces of our literature found various uses of AI. In the field of biology, including AI in the field of biology used for biological data analysis, genetic data analysis, investigation of complex biological phenomena (synthetic biology and system biology), bioinformatics, disease detection, and diagnosis. AI had been utilized in various fields of biological sciences such as medical, agriculture, animal husbandry, and industry for product development and automation in the production process utilizing IoT. There were 24 types of AI utilization in education, especially biology learning, which can be grouped into six groups: personalized and tutoring learning (teaching assistance/tutor), evaluation and assessment, teaching media, enriching learning, virtual classes, and learning aids.